Evidence that communication impairment in schizophrenia is associated with generalized poor task performance. (March 2017) - Merrill, Anne M.; Karcher, Nicole R.; Cicero, David C.; Becker, Theresa M.; Docherty, Anna R.; Kerns, John G.
Abstract: People with schizophrenia exhibit wide-ranging cognitive deficits, including slower processing speed and decreased cognitive control. Disorganized speech symptoms, such as communication impairment, have been associated with poor cognitive control task performance (e.g., goal maintenance and working memory). Whether communication impairment is associated with poorer performance on a broader range of non-cognitive control measures is unclear. In the current study, people with schizophrenia ( n =51) and non-psychiatric controls ( n =26) completed speech interviews allowing for reliable quantitative assessment of communication impairment. Participants also completed multiple goal maintenance and working memory tasks. In addition, we also examined (a) simple measures of processing speed involving highly automatic prepotent responses and (b) a non-cognitive control measure of general task performance. Schizophrenia communication impairment was significantly associated with poor performance in all cognitive domains, with the largest association found with processing speed ( r s =−0.52). Further, communication impairment was also associated with the non-cognitive control measure of poor general task performance ( r s =−0.43). In contrast, alogia, a negative speech symptom, and positive symptoms were less if at all related to cognitive task performance. Overall, this study suggests that communication impairment in schizophrenia may be associated with relatively generalized poor cognitive task performance. Highlights: Schizophrenia patients have deficits on cognitive control and basic cognitive tasks. Communication impairment is associated with cognitive deficits across domains. Negative and positive symptoms are not associated with cognitive deficits. Cognitive control does not predict speech impairment beyond basic cognitive tasks.